Etika Bisnis E-Commerce Shopee Berdasarkan Maqashid Syariah Dalam Mewujudkan Keberlangsungan Bisnis - Ruslang Ruslang; Muslimin Kara; Abdul Wahab (Jurnal Ilmiah Ekonomi Islam, 2020)
This study discusses Shopee's e-commerce business ethics based on maqashid sharia in realizing business continuity. Business ethics are the foundation of contemporary business because buyers and sellers do not meet in person. Maintaining the trust of two parties, an absolute requirement for online trading, it is important to apply business ethics based on maqashid sharia. The implication of this is the building of mutual trust between buyers, sellers and Shopee online stores. This study aims to reveal the implications of implementing business ethics based on maqashid sharia at Shopee. This research method uses descriptive qualitative research with field research. In the research results, Shopee applies business ethics based on maqashid sharia so that buyers are increasing and sellers are more loyal and Shopee's business continuity is getting stronger.